PERBEDAAN BAHAN STEK DAN KOMPOSISI MEDIA PADA PEMBIBITAN TANAMAN BUAH NAGA(Hylocereus costaricensis) - ', Surtono '; ', Wardati '; ', Armaini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Dragon fruit plant (Hylocereuscostaricensis) is one character of fruit crops that produce well in Indonesia that has a big opportunity to build up.These opportunities must be equilibrated by the provision of seedlings. Media and stem cuttings are a factor that must be considered in the nursery because it will affect the growth of seedlings in the field. This research was conducted in the village of dragon fruit plantations Tameran District of Bengkalis, Bengkalis. Time used in this study is four (4) months, going from early August to November 2012. The design used was completely randomized design (CRD) factorial 3 x 3 with three replications. The first factor is a stem cuttings, which is derived from the base, middle and tip cuttings. The second factor is the composition of the media, namely peat, peat and compost mixture of oil palm bunches (EFB) 3: 1 mixture of peat and sago dregs  3: 1. The parameters those measured were:  the number of roots, root length, root volume, shootsemergence time, shoot length, number of buds, seedling fresh weight and dry weight of seedlings. Data were analyzed statistically using Analysis Of Variance (ANOVA) up to a further test Honestly Significant Difference (HSD) level of 5%. Based on the results of this study concluded that the stem cuttings is best cuttings derived from the middle as it gives a significantly different effect on the parameters of shoot length and fresh weight and showing shoots of the fastest growing on the time parameters appear shoots and shows dry weight of the highest in the parameter dry weight seedlings . While on treatment composition of the medium obtained composition best media is derived from peat and compost TKKS (3 : 1) because it gives a significantly different effect on the parameters of the number of shoots and shows the root length of the longest on the parameters of the length of roots, shoots the fastest growing at the time parameters shoots appear and the highest weight on the parameters of fresh weight and dry weight of seedlings. And for the combined treatment of stem cuttings and the composition of the media influence that were not significantly different.   Keywords: dragon fruit, stem cuttings, media composition.